Soil stabilizer for silty clay and silty clay curing method

By using soil curing agents of mineral powder, waste ceramic powder, modified calcium carbide slag and nanonucleation agent, combined with alkali excitation system, the silty clay is cured, which solves the problems of insufficient strength and poor stability caused by the incompatibility of silty clay with cement-based materials, achieves the curing effect of high strength and durability, and promotes the reuse of industrial solid waste.

CN119707330APending Publication Date: 2025-03-28FOSHAN TRANSPORTATION SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656049.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Because silty clay has fine particles and is not suitable for cement-based curing agents, it leads to insufficient strength and poor stability, which limits its application in engineering.

Method used

A soil curing agent is used, including mineral powder, waste ceramic powder, modified calcium carbide slag and nanonucleation agent, and the silty clay is cured by an alkali-exciting system.

Benefits of technology

It effectively improves the strength and durability of silty clay, solves the problems of insufficient strength and poor stability caused by the incompatibility of cement-based materials and silty clay, and promotes the reuse of industrial solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005142136860000101
    Figure BDA0005142136860000101
Patent Text Reader

Abstract

The invention discloses a soil stabilizer for silty clay and a silty clay curing method. The soil stabilizer for silty clay comprises the following components in parts by weight: 50-70 parts of mineral powder, 5-30 parts of waste ceramic powder, 5-20 parts of carbide slag and 1-6 parts of a nano nucleating agent. By implementing the soil stabilizer and the curing method, industrial solid waste can be fully utilized, the problem that silty clay is difficult to form is solved, and the silty clay cured by using the soil stabilizer and the curing method is high in strength and good in durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials and environmental engineering, and in particular to a soil solidifying agent for silty clay and a silty clay solidifying method. Background Art

[0002] With the acceleration of industrialization, the discharge of industrial solid waste has increased year by year. These industrial solid wastes not only occupy a large amount of land resources, but also cause great pressure on the environment. Traditional treatment methods are mostly stacking or simple burial, which has the potential of waste of resources and pollution. Moreover, these industrial solid wastes contain a large amount of active ingredients such as silicate and calcium oxide, which have potential utilization value.

[0003] With the continuous progress of urbanization in my country, road traffic has developed more and more rapidly. However, this has led to the massive consumption of natural resources such as river sand and gravel, and the large amount of waste soil generated in engineering construction has nowhere to be piled. These problems have led to rising resource prices and increasingly prominent ecological and environmental pressures, which have seriously hindered the progress of engineering construction. In order to solve the above problems, many projects adopt the method of "taking soil on site" during construction, and solidify the waste soil generated on the project site with cement and other materials, thereby effectively reducing the demand for traditional building materials. Among them, silty clay, as a common engineering waste soil, is often hoped to be used. However, due to its fine particles and poor adaptability to cement, silty clay often has problems such as insufficient strength and poor stability when used directly, which limits its application effect in engineering. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a soil solidifying agent for silty clay and a silty clay solidification method, which can make full use of industrial solid waste, solve the problem of difficult molding of silty clay, and the solidified silty clay has high strength and good durability.

[0005] In order to solve the above problems, the present invention discloses a soil solidifier for silty clay, comprising the following components in parts by weight: 50-70 parts of mineral powder, 5-30 parts of waste ceramic powder, 5-20 parts of carbide slag, and 1-6 parts of nano nucleating agent.

[0006] As an improvement of the above technical solution, the mass ratio of the waste ceramic powder to the mineral powder is 0.3 to 0.6.

[0007] As an improvement of the above technical solution, the carbide slag is modified carbide slag, and the modified carbide slag includes the following raw materials in weight percentage: 15% to 40% carbide slag, 0.12% to 0.68% methacrylic acid, 0.03% to 0.12% sodium vinyl sulfonate, and 70% to 85% water.

[0008] As an improvement of the above technical solution, the carbide slag includes the following components in weight percentage: CaO 70% to 90%, Al2O3 1% to 5%, SiO2 2% to 8%, MgO 0.1% to 0.5%, SO3 2% to 6%, Fe2O3 0.1% to 0.5%, TiO2 0.01% to 0.1%, and LOI 20% to 30%.

[0009] As an improvement of the above technical solution, the specific surface area of ​​the waste ceramic powder is 400m 2 / kg~600m 2 / kg;

[0010] The waste ceramic powder comprises the following components in weight percentage: CaO 1% to 5%, SiO2 12% to 21%, A12O3 60% to 75%, Fe2O3 1% to 3%, Na2O 1% to 5%, MgO 1% to 5%, and LOI 1% to 5%.

[0011] As an improvement of the above technical solution, the mineral powder includes the following components in weight percentage: SiO2 30% to 40%, CaO 38% to 50%, MgO 5% to 10%, Al2O3 12% to 20%, Fe2O3 1% to 1.5%, Na2O 0.2% to 0.6%, K2O 0.2% to 0.5%, and LOI 1% to 5%.

[0012] As an improvement of the above technical solution, the nano nucleating agent is one or more of nano TiO2, carbon nanotubes, and graphene oxide.

[0013] Correspondingly, the present invention also discloses a method for solidifying silty clay, comprising the following steps:

[0014] (1) pre-treating the silty clay and storing it in a dry environment for standby use; the particle size of the pre-treated silty clay is ≤5 mm;

[0015] (2) mixing the pretreated silty clay and a soil solidifying agent in proportion and stirring evenly to obtain a mixture; the mass ratio of the soil solidifying agent to the silty clay is 8% to 13%;

[0016] (3) The mixture is statically pressed to obtain a standard test piece, which is sealed and placed under standard curing conditions for curing until the desired age is reached to obtain solidified silty clay.

[0017] As an improvement of the above technical solution, step (2) includes:

[0018] (2.1) Mix water and nano-nucleating agent in proportion and stir evenly, and perform ultrasonic treatment for more than 4 hours to obtain a mixed solution;

[0019] (2.2) mixing the pretreated silty clay, carbide slag, mineral powder and waste ceramic powder in proportion and stirring evenly to obtain a mixed soil;

[0020] (2.3) Mix the mixed liquid with the mixing soil and stir evenly to obtain a mixture.

[0021] As an improvement of the above technical solution, the natural moisture content of the silty clay is 25% to 35%, and the plasticity index is 10 to 16;

[0022] In step (2), water is also added during the mixing of the soil solidifier and the silty clay; the amount of water used is determined according to the optimal moisture content of the silty clay.

[0023] The implementation of the present invention has the following beneficial effects:

[0024] 1. The present invention solidifies silty clay by replacing the traditional cement-based system with an industrial solid waste alkali activation system, effectively improving the problems of insufficient strength and poor stability caused by the incompatibility of cement-based materials with silty clay.

[0025] 2. The present invention introduces nano nucleating agents to ensure that the early strength of the silty clay increases rapidly after solidification, and also effectively avoids the late - Insufficient water leads to incomplete hydration reaction.

[0026] 3. The present invention achieves a synergistic effect with other industrial solid wastes by introducing waste ceramic powder, which not only improves the later strength of the solidified silty clay, but also provides a new idea for solving the problems of solid waste treatment. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.

[0028] The invention provides a soil solidifying agent for silty clay, comprising the following components in parts by weight: 50 to 70 parts of mineral powder, 5 to 30 parts of waste ceramic powder, 5 to 20 parts of alkali activator, and 1 to 6 parts of nano nucleating agent.

[0029] Silty clay is mainly composed of kaolinite, and is interspersed with quartz, frog stone, illite, mica, etc. It has the characteristics of low water content, high density, low compressibility, high strength, etc. Specifically, the silty clay includes the following weight percentage components: SiO2 50% to 60%, Al2O3 20% to 30%, Fe2O3 2% to 8%, CaO2% to 8%, K2O 2% to 5%, MgO 1.8% to 2.2%, Na2O 0.8% to 1.8%, SO3 1% to 1.5%, LOI 1% to 5%. The particles of silty clay are relatively fine, and the adaptability to cement-based curing agents is not good. The silty clay cured with cement-based curing agents often has problems such as insufficient strength and poor stability when used. Therefore, the present invention uses an alkali-activated system of industrial solid waste materials to replace the traditional cement-based system to cure the silty clay, which effectively improves the problems of insufficient strength and poor stability caused by the incompatibility of cement-based curing agents with silty clay. During the solidification process, a large amount of OH in the soil environment - Ca on the surface of industrial solid waste materials 2+ and Mg 2+ React to generate Ca(OH)2 and Mg(OH)2. These reactions dissolve the glass surface of the industrial solid waste material, and as the reaction proceeds, the glass further disintegrates. At the same time, Ca(OH)2 reacts with SiO2 and Al2O3 in the industrial solid waste material to generate CSH gel and CASH gel. These gels fill the voids, improve the soil structure, and further achieve densification and hardening. Among them, the industrial solid waste material uses waste ceramic powder, which not only improves the later strength of the silty clay after solidification, but also achieves synergy with other industrial solid waste materials, providing new ideas for solving problems such as solid waste treatment. In addition, the introduction of nano-nucleating agents in the solidification process not only ensures the rapid increase in the early strength of the silty clay after solidification, but also effectively avoids the later period due to OH - Insufficient water leads to incomplete hydration reaction.

[0030] In a preferred embodiment, the mass ratio of waste ceramic powder to mineral powder is 0.3 to 0.6. If the mass ratio of waste ceramic powder to mineral powder is less than 0.3, there is not enough waste ceramic powder to hydrate and improve the strength, resulting in low late strength of the solidified silty clay; if the mass ratio of waste ceramic powder to mineral powder is greater than 0.6, some waste ceramic powder fails to participate in the hydration reaction, resulting in insufficient active substances in the soil solidifier, and the strength and durability of the test piece are reduced.

[0031] The raw materials of general solid waste powder soil solidifiers are relatively complex, mainly industrial solid wastes such as slag, coal gangue, desulfurized gypsum, steel slag, etc., mixed with auxiliary materials such as inorganic salts and latex powder. There are large differences in the origin and performance indicators of these raw materials, which leads to unstable performance of the final product. The industrial solid waste used in the present invention is mainly mineral powder, waste ceramic powder and carbide slag, which can not only realize the large-scale reuse of mineral powder, waste ceramic powder and carbide slag, but also make the performance of the soil solidifier more stable due to the small number of raw material types.

[0032] Among them, mineral powder is industrial solid waste produced during the blast furnace metal smelting process. Its main component is calcium aluminosilicate, and it exists in the form of glass. The glass structure of mineral powder is a phase structure, mainly composed of calcium-rich phase and a small amount of silicon-rich phase. Since mineral powder belongs to calcium-rich ore materials, it has high volcanic ash activity. In the early stage of the reaction, the mineral powder is in OH - Under the action of , the calcium-rich phase begins to decompose and gradually penetrates into the silicon-rich phase, releasing abundant silicon, calcium, aluminum and other elements. These elements enter the solution in the form of ions and recombine to form CSH gel and CASH gel. These gels fill the pores to form a network structure, which significantly improves the soil structure, thereby further improving the compactness and hardening effect of the soil. Specifically, the mineral powder includes the following weight percentages: SiO2 30% to 40%, CaO 38% to 50%, MgO 5% to 10%, Al2O3 12% to 20%, Fe2O3 1% to 1.5%, Na2O 0.2% to 0.6%, K2O 0.2% to 0.5%, LOI 1% to 5%. SiO2, CaO and Al2O3 can effectively improve the strength and durability of solidified silty clay, Fe2O3 can effectively control soil shrinkage, and alkaline oxides such as MgO, Na2O and K2O can reduce the binding capacity between soil particles and water and enhance the stability of the soil.

[0033] As an industrial solid waste, waste ceramic powder is a calcium-poor mineral material. The silicon-oxygen tetrahedron polymerization degree in its glass structure network is high and forms a three-dimensional network structure, resulting in low volcanic ash activity and slow dissolution of the glass in an alkaline environment. In the early stage of the reaction, the waste ceramic powder acts as fine aggregate, filling the pore structure in the soil and improving the compactness and stability of the soil. Over time, the glass structure gradually dissolves and generates many silicate ions and aluminate ions on the surface. These ions then undergo polycondensation with the calcium ions present in the system, and the system begins to gel, forming NASH gel, which is further reorganized into a gel network. The gel network formed by the waste ceramic powder provides favorable support for the strength skeleton of the entire reaction system and is the main source of the later strength of the improved silty clay. At the same time, it fills the pores left and formed in the early process of the entire reaction system, plays a role in refining the pore structure in the system, and further enhances the strength of the improved silty clay.

[0034] In a preferred embodiment, the specific surface area of ​​the waste ceramic powder is 400 m 2 / kg~600m 2 / kg, exemplified by 420m 2 / kg, 450m 2 / kg、500m 2 / kg, 520m 2 / kg or 550m 2 / kg, but not limited to this. If the specific surface area of ​​the waste ceramic powder is less than 400m 2 / kg, affecting the hydration rate; if the specific surface area of ​​the waste ceramic powder is greater than 600m 2 / kg, which will increase the porosity and is not conducive to improving the overall strength. Specifically, the waste ceramic powder includes the following components in weight percentage: CaO 1% to 5%, SiO2 12% to 21%, A12O3 60% to 75%, Fe2O3 1% to 3%, Na2O 1% to 5%, MgO 1% to 5%, LOI 1% to 5%. Under this condition, the waste ceramic powder has enough active substances to react with the calcium ions in the system to undergo polycondensation, cement the silty clay particles, and improve the strength of the soil.

[0035] Optionally, the alkaline activator is carbide slag. When the alkaline activator is dissolved in water, OH is rapidly released. - Part of it reacts with the active ingredients in the clay particles in the soil to produce volcanic ash, improving the strength of the soil itself; the remaining part is adsorbed on the nano-nucleating agent, precipitates and crystallizes in the form of hydroxide, interspersed between the gaps between soil particles to form a strong skeleton, while avoiding excessive OH -React with soil particles to ensure the later strength development. Commonly used strong alkaline activators are mainly sodium hydroxide or water glass, but in terms of economy, their prices are too expensive and not conducive to large-scale engineering applications. Calcium carbide slag is the waste residue after acetylene gas is produced from calcium carbide. Its main component is Ca(OH)2, and there are also small amounts of SiO2, Fe2O3, Al2O3, MgO and other substances. As an industrial solid waste material, calcium carbide slag is widely available and cheap, which can significantly reduce production costs. In addition, in addition to providing an alkaline environment suitable for the reaction of solid waste materials such as mineral powder, calcium carbide slag can also provide rich OH - and Ca 2+ , which helps to promote the formation of CSH gel in the reaction system and improve the early strength of modified silty clay. Specifically, carbide slag includes the following weight percentages: CaO 70% to 90%, Al2O3 1% to 5%, SiO2 2% to 8%, MgO 0.1% to 0.5%, SO3 2% to 6%, Fe2O3 0.1% to 0.5%, TiO2 0.01% to 0.1%, and LOI 20% to 30%. CaO determines the ability of carbide slag to provide an alkaline environment. If the mass percentage of CaO is too low, it is difficult to provide a sufficient alkaline environment and cannot stimulate the production of enough gel products, resulting in a decrease in soil strength after solidification; if the mass percentage of CaO is too high, it will increase the amount of water required for soil solidification, which is not conducive to construction use. Using carbide slag as an alkali activator in the solidification of silty clay can not only ensure the performance of solid waste materials under alkali activation, but also further make full use of industrial solid waste materials.

[0036] In a preferred embodiment, the alkaline activator is modified carbide slag, specifically, the modified carbide slag includes the following raw materials in weight percentage: 15% to 40% carbide slag, 0.12% to 0.68% methacrylic acid, 0.03% to 0.12% sodium vinyl sulfonate, and 70% to 85% water. The preparation method of modified carbide slag includes: reacting methacrylic acid with sodium vinyl sulfonate at a temperature of 75°C to 85°C, and then mixing with carbide slag and stirring evenly to obtain. Using carbide slag alone as an alkaline activator may cause the early strength of silty clay solidified by a soil solidifying agent using waste ceramic powder as a raw material to decrease. The present invention uses modified carbide slag as an alkaline activator to accelerate the hydration rate, so that calcium hydroxide is more evenly distributed in silty clay and solid waste materials, and improves early strength; and the carbide slag also plays a filling role, reducing the porosity while optimizing the pore structure, avoiding the problems of insufficient strength and poor stability that may occur after the silty clay is solidified.

[0037] Optionally, the nano nucleating agent is one or more of nano TiO2, carbon nanotubes, and graphene oxide. During the preparation process, the nano nucleating agent after ultrasonic treatment is dispersed in water, and is evenly dispersed in the mixed soil during the stirring process of the mixed soil composed of water, silty clay, and industrial solid waste materials. These nano nucleating agents provide additional nucleation sites for hydration products and promote the production of hydration products by reducing the energy barrier of the nucleation interface and improving the hydration environment, thus acting as an early strength agent. Finally, after the mixture is fully extruded and formed, the porosity of the soil body is greatly reduced, the contact between the components is more sufficient, and the soil body has generated initial strength. Moreover, some alkali activators can also be adsorbed on the nano nucleating agent, precipitate crystals in the form of hydroxides, and intersperse between the gaps between soil particles to form a strength skeleton, while avoiding excessive OH - Reacts with soil particles to ensure later strength development.

[0038] Correspondingly, the present invention also discloses a method for solidifying silty clay, comprising the following steps:

[0039] (1) Pre-treat the silty clay and store it in a dry environment for standby use; the particle size of the pre-treated silty clay is ≤5 mm; in one embodiment, after the large pieces of silty clay are broken into small pieces, they are placed in an oven at 105°C and heated for more than 8 hours until they are completely dried. Then, the dried silty clay is ground and sieved through a 5 mm sieve to obtain the pre-treated silty clay. Specifically, the silty clay is excavated soil from a capital construction project in Foshan City. The natural moisture content of the silty clay is 25% to 35%, the plasticity index is 10 to 16, and the particle size is ≤5 mm.

[0040] (2) The pretreated silty clay and the soil solidifier are mixed and stirred uniformly in proportion to obtain a mixture; the mass ratio of the soil solidifier to the silty clay is 8% to 13%, and exemplarily 9%, 9.5%, 10%, 11% or 12%, but not limited thereto. A mass ratio that is too high may result in a decrease in the strength of the improved silty clay, and a mass ratio that is too low may fail to achieve the expected solidification effect. The specific mass ratio can be adjusted according to the use requirements.

[0041] In a preferred embodiment, step (2) comprises:

[0042] (2.1) Mix water and nano nucleating agent in proportion and stir evenly, and perform ultrasonic treatment for more than 4 hours to obtain a mixed solution; specifically, the amount of water is determined according to the optimal moisture content of the improved silty clay. It should be noted that the amount of water is not included in the mass of the soil stabilizer, that is, in the mass ratio of the soil stabilizer to the silty clay, the mass of the soil stabilizer does not include the amount of water.

[0043] (2.2) Mixing the pretreated silty clay, alkali activator, mineral powder and waste ceramic powder in proportion and stirring evenly to obtain mixed soil;

[0044] (2.3) The mixed liquid is mixed with the mixed soil and stirred evenly to obtain a mixture; during the preparation process, the weight of the components required for molding a single standard specimen is determined based on the maximum dry density.

[0045] (3) The mixture is statically pressed to obtain a standard specimen and sealed, and then placed under standard curing conditions for curing until the required age is reached to obtain solidified silty clay. Specifically, the mixture is statically pressed into a cylindrical standard specimen with a diameter of 100 mm and a height of 100 mm using an oil press, and then cured according to the relevant provisions of CJJ / T 286-2018 "Technical Standard for Application of Soil Stabilizers".

[0046] The present invention will be further described below with specific embodiments:

[0047] Example 1

[0048] The present embodiment provides a soil solidifier for silty clay, comprising the following components in parts by weight: 60 parts of mineral powder, 8 parts of waste ceramic powder, 8 parts of carbide slag, and 4 parts of nano-TiO2.

[0049] The specific surface area of ​​waste ceramic powder is 400m 2 / kg, the waste ceramic powder includes the following components: CaO 7.67%, SiO265.72%, A12O3 18.31%, Fe2O3 1.28%, Na2O 1.65%, MgO 1.21%, LOI 4.16%.

[0050] The mineral powder includes the following components in weight percentage: SiO2 32.96%, CaO 40.13%, MgO 6.28%, Al2O3 15.27%, Fe2O3 1.15%, Na2O 0.36%, K2O 0.31%, and LOI 3.54%.

[0051] Example 2

[0052] The present embodiment provides a soil solidifier for silty clay, comprising the following components in parts by weight: 52 parts of mineral powder, 16 parts of waste ceramic powder, 8 parts of carbide slag, and 4 parts of nano-TiO2.

[0053] The specific surface area of ​​waste ceramic powder is 400m 2 / kg, the waste ceramic powder includes the following components: CaO 7.67%, SiO265.72%, A12O3 18.31%, Fe2O3 1.28%, Na2O 1.65%, MgO 1.21%, LOI 4.16%.

[0054] The mineral powder includes the following components in weight percentage: SiO2 32.96%, CaO 40.13%, MgO 6.28%, Al2O3 15.27%, Fe2O3 1.15%, Na2O 0.36%, K2O 0.31%, and LOI 3.54%.

[0055] The carbide slag includes the following components in weight percentage: CaO 62.20%, Al2O3 3.25%, SiO2 5.13%, MgO 0.42%, SO3 2.14%, Fe2O3 0.47%, TiO2 0.08%, and LOI 26.31%.

[0056] Example 3

[0057] The present embodiment provides a soil solidifier for silty clay, comprising the following components in parts by weight: 44 parts of mineral powder, 24 parts of waste ceramic powder, 8 parts of carbide slag, and 4 parts of nano-TiO2.

[0058] The specific surface area of ​​waste ceramic powder is 400m 2 / kg, the waste ceramic powder includes the following components: CaO 7.67%, SiO265.72%, A12O3 18.31%, Fe2O3 1.28%, Na2O 1.65%, MgO 1.21%, LOI 4.16%.

[0059] The mineral powder includes the following components in weight percentage: SiO2 32.96%, CaO 40.13%, MgO 6.28%, Al2O3 15.27%, Fe2O3 1.15%, Na2O 0.36%, K2O 0.31%, and LOI 3.54%.

[0060] The carbide slag includes the following components in weight percentage: CaO 62.20%, Al2O3 3.25%, SiO2 5.13%, MgO 0.42%, SO3 2.14%, Fe2O3 0.47%, TiO2 0.08%, and LOI 26.31%.

[0061] Example 4

[0062] The present embodiment provides a soil solidifier for silty clay, comprising the following components in parts by weight: 36 parts of mineral powder, 32 parts of waste ceramic powder, 8 parts of carbide slag, and 4 parts of nano-TiO2.

[0063] The specific surface area of ​​waste ceramic powder is 400m 2 / kg, the waste ceramic powder includes the following components: CaO 7.67%, SiO265.72%, A12O3 18.31%, Fe2O3 1.28%, Na2O 1.65%, MgO 1.21%, LOI 4.16%.

[0064] The mineral powder includes the following components in weight percentage: SiO2 32.96%, CaO 40.13%, MgO 6.28%, Al2O3 15.27%, Fe2O3 1.15%, Na2O 0.36%, K2O 0.31%, and LOI 3.54%.

[0065] The carbide slag includes the following components in weight percentage: CaO 62.20%, Al2O3 3.25%, SiO2 5.13%, MgO 0.42%, SO3 2.14%, Fe2O3 0.47%, TiO2 0.08%, and LOI 26.31%.

[0066] Example 5

[0067] The present embodiment provides a soil solidifier for silty clay, comprising the following components in parts by weight: 60 parts of mineral powder, 8 parts of waste ceramic powder, 8 parts of modified carbide slag, and 4 parts of nano-TiO2.

[0068] The specific surface area of ​​waste ceramic powder is 400m 2 / kg, the waste ceramic powder includes the following components: CaO 7.67%, SiO265.72%, A12O3 18.31%, Fe2O3 1.28%, Na2O 1.65%, MgO 1.21%, LOI 4.16%.

[0069] The mineral powder includes the following components in weight percentage: SiO2 32.96%, CaO 40.13%, MgO 6.28%, Al2O3 15.27%, Fe2O3 1.15%, Na2O 0.36%, K2O 0.31%, and LOI 3.54%.

[0070] The carbide slag includes the following components in weight percentage: CaO 62.20%, Al2O3 3.25%, SiO2 5.13%, MgO 0.42%, SO3 2.14%, Fe2O3 0.47%, TiO2 0.08%, and LOI 26.31%.

[0071] The modified carbide slag comprises the following raw materials in weight percentage: 25% carbide slag, 0.2% methacrylic acid, 0.05% sodium vinyl sulfonate, and 74.75% water. The preparation method of the modified carbide slag comprises: reacting methacrylic acid with sodium vinyl sulfonate at 80°C, and then mixing with the carbide slag and stirring evenly to obtain the modified carbide slag.

[0072] Comparative Example 1

[0073] This comparative example provides a soil stabilizer for silty clay, comprising the following components in parts by weight: 68 parts of mineral powder, 8 parts of carbide slag, and 4 parts of nano-TiO2.

[0074] Comparative Example 2

[0075] This comparative example provides a soil solidifier for silty clay, comprising the following components in parts by weight: 80 parts of cement.

[0076] Example 6

[0077] This embodiment provides a method for solidifying silty clay, comprising the following steps:

[0078] (1) pre-treating the silty clay and storing it in a dry environment for future use; the particle size of the pre-treated silty clay is ≤5 mm;

[0079] (2.1) Take 160 parts of water, mix with the nano nucleating agent and stir evenly, and perform ultrasonic treatment for more than 4 hours to obtain a mixed solution;

[0080] (2.2) 760 parts of the pretreated silty clay are mixed with an alkali activator, mineral powder and waste ceramic powder and stirred evenly to obtain a mixed soil;

[0081] (2.3) Mixing the mixed liquid with the mixing soil and stirring them evenly to obtain a mixture;

[0082] (3) The mixture is statically pressed into a cylindrical standard specimen with a diameter of 100 mm and a height of 100 mm, and cured according to the provisions of CJJ / T286-2018 "Technical Standard for Application of Soil Stabilizers" until the required age is reached to obtain solidified silty clay.

[0083] The soil solidifying agents provided in Examples 1 to 5, Comparative Examples 1 and 2 were used to solidify the silty clay using the soil solidification method of Example 6, and the unconfined compressive strength test and freeze-thaw cycle test were performed on the solidified silty clay according to JTG E51-2009 "Test Procedure for Inorganic Binders". The specific results are as follows:

[0084]

[0085] According to the unconfined compressive strength test data, it can be seen that the early and late strengths of the solidified silty clay in Comparative Example 1 using cement as the soil solidifier are significantly lower than those of the silty clay solidified by the soil solidifier used in the embodiment of the present invention. This is because the alkali activator in the soil solidifier provides a large amount of OH - , plus the nano-nucleating agent provides nucleation sites to avoid excessive OH - React with clay particles to ensure the alkaline environment required for the hydration reaction. Comparative Example 2 to Example 4 and Comparative Example 2, although the incorporation of waste ceramic powder will affect the early strength of the improved silty clay, with the increase of the amount of waste ceramic powder added, the later strength of the improved silty clay shows a trend of first rising and then decreasing. This is because the activity of the waste ceramic powder is relatively low, and the hydration rate is slower than other solid waste materials, resulting in its low early strength, but with the development of time, when the hydration of other solid wastes is basically stopped (the remaining part can only serve as an aggregate), the hydration product of the waste ceramic powder becomes the main source of strength improvement, so the incorporation of waste ceramic powder can effectively improve the later strength. However, when the amount of waste ceramic powder added is too high, some of the waste ceramic powder fails to participate in the hydration reaction, resulting in insufficient active substances in the soil curing agent and reduced strength of the test piece. As can be seen from Example 5, by preferably alkali activators, the early strength can be further improved while ensuring the later strength.

[0086] According to the freeze-thaw cycle test data, it can be seen that the improved silty clay specimen of Comparative Example 1 disintegrated after the freeze-thaw test, and there were obvious cracks in the main part of the specimen. The silty clay improved by the soil solidifier provided by the embodiment of the present invention has very obvious advantages in both compressive strength and mass loss, and has relatively excellent durability. Comparing Examples 2 to 4 with Comparative Example 2, with the increase of the amount of waste ceramic powder added, the compressive strength and mass loss of the silty clay showed a trend of first increasing and then decreasing. This is because the waste ceramic powder hydration speed is slow, and the hydration heat released during the hydration process is low, resulting in fewer cracks caused by hydration heat; at the same time, the waste ceramic powder can repair small cracks formed due to shrinkage and other reasons during the hydration process. Therefore, in the early stage, with the increase of the amount of waste ceramic powder added, the inside of the specimen became more and more compact. However, when the amount of waste ceramic powder added increases to a certain extent, some of the waste ceramic powder fails to participate in the hydration reaction, resulting in insufficient active substances in the soil solidifier and a decrease in the durability of the specimen. Example 5 preferably uses an alkali activator to improve the durability of the silty clay.

[0087] In summary, the silty clay solidified by the soil solidifier provided by the embodiment of the present invention has excellent mechanical properties and durability.

[0088] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A soil solidifying agent for silty clay, characterized in that: The invention comprises the following components in parts by weight: 50-70 parts of mineral powder, 5-30 parts of waste ceramic powder, 5-20 parts of carbide slag and 1-6 parts of nano nucleating agent.

2. The soil solidifying agent for silty clay according to claim 1, characterized in that: The mass ratio of the waste ceramic powder to the mineral powder is 0.3 to 0.

6.

3. The soil solidifying agent for silty clay according to claim 1, characterized in that: The carbide slag is modified carbide slag, which includes the following raw materials in weight percentage: 15% to 40% carbide slag, 0.12% to 0.68% methacrylic acid, 0.03% to 0.12% sodium vinyl sulfonate, and 70% to 85% water.

4. The soil solidifying agent for silty clay according to claim 3, characterized in that: The carbide slag comprises the following components in weight percentage: CaO 60%-90%, Al2O3 1%-5%, SiO2 2%-8%, MgO 0.1%-0.5%, SO3 2%-6%, Fe2O3 0.1%-0.5%, TiO2 0.01%-0.1%, and LOI 20%-30%.

5. The soil solidifying agent for silty clay according to claim 3, characterized in that: The specific surface area of ​​the waste ceramic powder is 400m 2 / kg~600m 2 / kg; The waste ceramic powder comprises the following components in weight percentage: CaO 1% to 8%, SiO2 60% to 75%, A12O3 12% to 21%, Fe2O3 1% to 3%, Na2O 1% to 5%, MgO 1% to 5%, and LOI 1% to 5%.

6. The soil solidifying agent for silty clay according to claim 1, characterized in that: The mineral powder comprises the following components in weight percentage: SiO2 30%-40%, CaO 38%-50%, MgO 5%-10%, Al2O3 12%-20%, Fe2O3 1%-1.5%, Na2O 0.2%-0.6%, K2O 0.2%-0.5%, and LOI 1%-5%.

7. The soil solidifying agent for silty clay according to claim 1, characterized in that: The nano nucleating agent is one or more of nano TiO2, carbon nanotubes, and graphene oxide.

8. A method for solidifying silty clay, characterized in that: The following steps are involved: (1) pre-treating the silty clay and storing it in a dry environment for standby use; the particle size of the pre-treated silty clay is ≤5 mm; (2) mixing the pretreated silty clay and a soil solidifying agent in proportion and stirring evenly to obtain a mixture; the mass ratio of the soil solidifying agent to the silty clay is 8% to 13%; (3) The mixture is statically pressed to obtain a standard test piece, which is sealed and placed under standard curing conditions for curing until the desired age is reached to obtain solidified silty clay.

9. The method for solidifying silty clay according to claim 8, characterized in that: Step (2) comprises: (2.1) Mix water and nano-nucleating agent in proportion and stir evenly, and perform ultrasonic treatment for more than 4 hours to obtain a mixed solution; (2.2) mixing the pretreated silty clay, carbide slag, mineral powder and waste ceramic powder in proportion and stirring evenly to obtain a mixed soil; (2.3) Mix the mixed liquid with the mixing soil and stir evenly to obtain a mixture.

10. The method for solidifying silty clay according to claim 8, characterized in that: The natural moisture content of the silty clay is 25% to 35%, and the plasticity index is 10 to 16; In step (2), water is also added during the mixing of the soil solidifier and the silty clay; the amount of water used is determined according to the optimal moisture content of the silty clay.